A resiliency framework for an enterprise cloud. Issue 1 (February 2016) - Chang, Victor; Ramachandran, Muthu; Yao, Yulin; Kuo, Yen-Hung; Li, Chung-Sheng
Highlights: We have presented a resilient framework for an enterprise cloud. We have developed an architecture with four major services to demonstrate resiliency, where the cloud computing adoption framework (CCAF) takes the center role to blend other services. We explain how our work is relevant to business resiliency. We have the support from a large scale survey to ensure that our design and service can meet the large number of user requirements. Abstract: This paper presents a systematic approach to develop a resilient software system which can be developed as emerging services and analytics for resiliency. While using the resiliency as a good example for enterprise cloud security, all resilient characteristics should be blended together to produce greater impacts. A framework, cloud computing adoption framework (CCAF), is presented in details. CCAF has four major types of emerging services and each one has been explained in details with regard to the individual function and how each one can be integrated. CCAF is an architectural framework that blends software resilience, service components and guidelines together and provides real case studies to produce greater impacts to the organizations adopting cloud computing and security. CCAF provides business alignments and provides agility, efficiency and integration for business competitive edge. In order to validate user requirements and system designs, a large scale survey has been conducted with detailed analysis provided for each major question. We present our discussion and conclude that the use of CCAF framework can illustrate software resilience and security improvement for enterprise security. CCAF framework itself is validated as an emerging service for enterprise cloud computing with analytics showing survey analysis.